Pressione turistica sul Centro Storico di Firenze - sito UNESCO Un modello per la valutazione dell'impatto percettivo - ROMANO, Ilenia Maria (Premio Tesi di Dottorato, 2018)
This research is part of the debate on sustainable tourism development and, in particular, on the impacts that tourist pressure generates in the cities of art: the analysis is indeed focused on the Historic Centre of Florence, which was admitted onto the World Heritage list in 1982. The site adopted a Management Plan which aims at, among other things, monitoring the five main threats, including tourism and the critical issues generated by its impacts. This study aims at developing a model for the improvement of the decision making process, using maps which represent the indicators developed through the analysis of pressure, status and impact factors as perceived by the local community and by a web mapping platform for integrated and participatory management. The tool is designed to be part of the monitoring envisaged by the Management Plan in order to implement controlled and shared management systems, improve dialogue between the different stakeholders, support the definition of strategies for the decentralization of tourist areas and decrease tourist pressure and the impacts it generates.